Sentencing Under The Special Minimum Threat For Small-Scale Drug Traffickers: Challenges And Implications For Justice And Drug Eradication Policy - Fitria, Ferisa Dian; Safa’at , Muchamad Ali; Madjid, Abdul (CV. AFDIFAL MAJU BERKAH, 2024)
The imposition of sentences below the minimum penalty specifically for small-scale drug dealers has become an important debate in the context of criminal justice. This study aims to analyze the practice of judicial independence in small-scale drug trafficking cases and identify the challenges and implications for substantive justice and drug eradication policy in Indonesia. The method used in this study is comparative normative juridical, this research analyses the applicable legal rules in Indonesia and compares them with practices in several other countries. The results show that the application of sentences below the special minimum threat has a significant influence on drug eradication policies, but also raises dilemmas related to justice for offenders with a small role. Comparatively, practices in other countries show a more flexible approach, which integrates restorative justice and rehabilitation principles. This study recommends the revision of legal policies in Indonesia by adopting a more proportional approach, as well as improved training of law enforcement officers to ensure fair and consistent application. This research is expected to contribute to the formation of a more effective, humane, and equitable drug policy.